Factor-Cluster Analysis in the Private Healthcare System of the Republic of Armenia - Aghajanyan, Susanna; Nikoghosyan, Marine; Badalyan, Meri; Vardanyan, Tatevik («Տնտեսագետ» հրատ․)
The study of the factors affecting the pricing of medical services in the private healthcare sector in the Republic of Armenia reveals several internal and external determining factors that significantly impact the pricing dynamics. This article mainly aims to evaluate the satisfaction level of patients from private medical institutions in Armenia through factor-cluster analysis. Eleven different factors were identified and classified according to two main variables: medical and maintenance. This article aims to measure patient satisfaction in different types and levels of healthcare facilities and determine which factors influence this level of satisfaction. In this article, we will discuss how these factors affect patient satisfaction levels. This paper also aims to develop a detailed conceptual model for understanding and quantifying the factors influencing the quality of care based on patient satisfaction. In the largest cluster, to which 70% of the respondents belong, individuals expressed dissatisfaction with the medical services offered by private medical facilities in Armenia, providing valuable insight into the nuances of patient satisfaction with the private healthcare sector in Armenia, shedding light on the areas in which they work that may be in need of improvement or further attention.
Keywords: Sectorial economics